Lecturer wins award for eco-friendly termite bait - UMP, PNC (The New Straits Times Press (M) Bhd., 2017)
KUANTAN: A Universiti Malaysia Pahang (UMP) lecturer's 12-year research into oil palm bunches for pest control bore fruit when he won the 2017 National Innovation Award (NIA) in the product category.